Алелопатична активність деяких видів родини Araceae Juss. - Ivanytska, B.O. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2008)
Experimental data for growth inhibitors content in soil and fruit, leaves, roots, seedlings of four species of Araceae Juss. family are presented. Water extracts (1:10) of different organs of experimental plants influenced on test-object (Lepidium sativum L.) roots growth in following sequence: extract from fruit > roots > leaves > seedlings.